2008
DOI: 10.4269/ajtmh.2008.78.289
|View full text |Cite
|
Sign up to set email alerts
|

Mass Drug Administration Trial to Eliminate Lymphatic Filariasis in Papua New Guinea: Changes in Microfilaremia, Filarial Antigen, and Bm14 Antibody after Cessation

Abstract: Laboratory tools to monitor infection burden are important to evaluate progress and determine endpoints in programs to eliminate lymphatic filariasis. We evaluated changes in Wuchereria bancrofti microfilaria, filarial antigen and Bm14 antibody in individuals who participated in a five-year mass drug administration trial in Papua New Guinea. Comparing values before treatment and one year after four annual treatments, the proportion of microfilaria positive individuals declined to the greatest degree, with less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
41
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 21 publications
7
41
0
Order By: Relevance
“…20 In our study, the prevalence of MF and intensity of antigenemia either remained static or significantly decreased ( P < 0.001), respectively, among children who received DEC. For children who received placebo, the intensity of antigenemia significantly increased ( P = 0.039) at the end of the study. As in other studies that showed decreased antibody responses to Bm14 by ELISA after DEC treatment, 20,[25][26][27][28] we showed decreases in antibody responses to Bm14 by MBA among children who received drugs containing DEC ( Figure 1A and B). Interestingly, antibody responses to Bm14 and Bm33 decreased among children who received drugs containing DEC, even among children who were MF-/ Og4C3-( Figures 1A and 2A ).…”
Section: Discussionsupporting
confidence: 60%
“…20 In our study, the prevalence of MF and intensity of antigenemia either remained static or significantly decreased ( P < 0.001), respectively, among children who received DEC. For children who received placebo, the intensity of antigenemia significantly increased ( P = 0.039) at the end of the study. As in other studies that showed decreased antibody responses to Bm14 by ELISA after DEC treatment, 20,[25][26][27][28] we showed decreases in antibody responses to Bm14 by MBA among children who received drugs containing DEC ( Figure 1A and B). Interestingly, antibody responses to Bm14 and Bm33 decreased among children who received drugs containing DEC, even among children who were MF-/ Og4C3-( Figures 1A and 2A ).…”
Section: Discussionsupporting
confidence: 60%
“…Several other publications have evaluated the IgG4 antibody detection to the rBm14 antigen as a monitoring tool post-MDA; however, most of them have obtained the rBm14 antigen directly from Dr Gary Weil's laboratory in Washington DC before Cellabs Pty Ltd of Australia developed the new kit (CELISA) in 2006 [6,18,19]. A study conducted by Ramzy just after the 5th round of MDA in 2 Egyptian villages reported that the antibody prevalence rates can take several years to fall to low levels after MDA [6].…”
Section: Discussionmentioning
confidence: 99%
“…24,[29][30][31] All sequences were 100% identical with the W. bancrofti sequence in GenBank (accession no. AY297458).…”
mentioning
confidence: 97%
“…32 Furthermore, we sequenced the PCR product from five pooled third-stage larvae dissected from mosquitoes that were collected in the Dreikikir District (East Sepik Province, Papua New Guinea), where malaria and lymphatic filariasis are endemic. 24,[29][30][31] All sequences were 100% identical with the W. bancrofti sequence in GenBank (accession no. AY297458).…”
mentioning
confidence: 97%
See 1 more Smart Citation